Passive smoking and risk of gestational diabetes mellitus: A systematic review and meta-analysis - Haijie Zhang+; Xin Zhou+; Lixia Tian; Jianjun Huang; Meng E; Jinzhu Yin (Tobacco Induced Diseases, 2023)
Introduction Pregestational smoking increases the risk of gestational diabetes mellitus (GDM) and is a common health problem during pregnancy, with its incidence on the rise worldwide, especially in China. This study is a meta-analysis of passive smoking as a risk factor associated with GDM.